INTERSPECIFIC HYBRIDIZATION IN THE GENUS SOLANUM L. AND ITS USE IN BREEDING - M. I. Mamedov; O. N. Pishnaya; N. A. Shmykova; V. A. Verba; E. A. Jos; T. P. Suprunova (Овощи России)
The studies found that in the crosses of S. melongena with wild species, used as a male and female component, the interspecific hybrids have the traits of the generative organs of wild species: the shape and flower size, color, shape and fruit size.